Hermeneutika Hukum dalam Metode Penelitian Hukum - Mahfud Mahfud (Universitas Syiah Kuala, 2014)
In philosophy perspective, hermeneutic is an philosophy branch exploring basic thing of understanding of something; that is aimed at are: texts (official documents), ancient literatures, norms, occasions, thoughts and divine as the objects of its interpretation. Thus, if the objects are legal texts, doctrines, principles, norms, the essence is legal hermeneutic. The relevance of the legal method is through legal hermeneutic based on research findings can be concluded: firstly, it can be understood as interpretation method or legal texts or the method of understanding on a normative document. Secondly, it is also having great impact or relevance with “legal findings’ theories”. Legal Hermeneutic in Legal Research Method